Dynamic absorber for self-excred system with distributed parameters (vibrating string) - Dao, Nguyen Van (Vietnam Journal of Mechanics, 1985)
The dynamic absorber may be used to damp the self - excited vibration or the string. The friction mechanism of absorber (λ) has decisive influence on the amplitude of self-exerted vibration of the string. For the strong dynamic absorber the increasing of the friction force (λ) leads to the decreasing of the amplitude or vibration of the string. For the weak dynamic absorber (m, c are small) the effect of damping will be achieved only with some mean values of the friction force.